Russian population’s political activities in the first third of the XX century on the example of the Peasant Union creation movement - G. S. Chuwardin; V. G. Ivanov; O. A. Nesterchuk; V. F. Nitsevich; O. A. Sudorgin (Управление)
The article studies peasantry’s political activities development in Russia in the first third of the XX century. The reasons and the essence of the Peasant Union in the revolutionary events of 1905–1907 and 1917, the Civil War and in the period of the new economic policy have been revealed. The periods of peasantry’s political activities, conditioned by the state policy transformation in village, have been distinguished. Starting from 1905, the authorities tried to involve peasantry in the political agenda. However, politicization could not be controlled in the conditions of the revolution. Peasantry’s political activities were used by the opposition forces, the SRs and Bolsheviks, who proposed a program understandable to the peasant social psychology. The Third Monarchy suspended the Peasant Union activities. In February 1917, the Union work continued under the control of the SRs. In August 1917, Peasant Congress adopted the SR program documents. Calls to create a union during the Civil War took place against the background of peasants’ disillusionment with the “war communism” policy. In 1921, the idea of creating the Peasant Union was revived. Contradictory nature of Bolshevik policy, the concept of “interlocking” between city and countryside, growing “emergency” and crises of the new economic policy against the background of granting peasants relative economic freedom led to peasant demands growth for protecting their economic rights and creating organizations that resembled trade unions in city. These demands were not institutionalized. The movement reached all strata of village. The surge of demands of the United State Political Department dates from 1927–1928. It is conditioned by the transition to collectivization. It has been concluded that, despite the lack of the Peasant Union concept, diversity of demands, different understanding of association in rural society, movement for its creation testified to increased socio-political activity of the population. When the state policy outlined the rollback of the new economic policy principles, the number of votes in favor of the Union increased. The growth of socio-political tension in villages was evident. The Party began to pursue a policy of social division in villages to prevent radicalization of sentiments.